Dielectric properties of single crystalline Ba(Ti0.99Zr0.01)2O5 prepared by the floating zone method. (2017) - Shiga, Keiji; Katsui, Hirokazu; Goto, Takashi
Abstract: Zr 4+ -substituted single crystalline BaTi2 O5 (Ba(Ti0.99 Zr0.01 )2 O5 ) was prepared by the floating zone method, and its dielectric properties were investigated. The growth direction of Ba(Ti0.99 Zr0.01 )2 O5 was parallel to the b axis. The Curie temperature of Ba(Ti0.99 Zr0.01 )2 O5 was 710 K, which was 42 K lower than that of BaTi2 O5 . The complex impedance plane plot of BaTi2 O5 in the b direction showed a semicircle associated with ferroelectric response and a spike associated with ionic conduction at 623 K. On the other hand, the complex impedance plot of Ba(Ti0.99 Zr0.01 )2 O5 showed a single semicircle, suggesting almost no ionic conduction. The electrical conductivity of Ba(Ti0.99 Zr0.01 )2 O5 was approximately half of that of BaTi2 O5 .